A World of Fiction : Digital Collections and the Future of Literary History - Bode, Katherine (Digital humanities (Ann Arbor, Mich.), 2018)
During the 19th century, throughout the Anglophone world, most fiction was first published in periodicals. In Australia, newspapers were not only the main source of periodical fiction, but the main source of fiction in general. Because of their importance as fiction publishers, and because they provided Australian readers with access to stories from around the world--from Britain, America and Australia, as well as Austria, Canada, France, Germany, New Zealand, Russia, South Africa, and beyond--Australian newspapers represent an important record of the transnational circulation and reception of fiction in this period. Investigating almost 10,000 works of fiction in the world's largest collection of mass-digitized historical newspapers (the National Library of Australia's Trove database), A World of Fiction reconceptualizes how fiction traveled globally, and was received and understood locally, in the 19th century. Katherine Bode's innovative approach to the new digital collections that are transforming research in the humanities are a model of how digital tools can transform how we understand digital collections and interpret literatures in the past.